Medical health knowledge management using wireless network: Moroccan hospitals case study - Jamaly, S.; Wongthongtham, Pornpit; Aseeri, Ahmed (IEEE, 2009)
Hospitals and medical health services are large business that we have to make them successful for their earned profits and incomes. Unifying the communication in hospitals can approve the environments and avoid the problems faced. Wireless networks are very useful in large crowded places like hospitals. Wireless technology has empowered the medical health systems by reducing the paperwork that nurses or doctors have to deal with them whole day. Its primary purpose is to ensure effective care of patients by increasing the accuracy and speed of health care. This paper highlights patients' knowledge management in hospitals using the wireless communication since the rate of medical errors has increased lately. The intention of this paper is to utilize an advanced technology to help hospitals raise the rate of care of patients throughout the use of mobile data collection device that transmits data to a centralized database to raise the visibility of data to the receivers.